Kebutuhan Berprestasi dalam Publikasi Ilmiah : FGD Mahasiswa BIB Kemenag LPDP Program Studi PAI Pascasarjana UIN Sunan Gunung Djati Bandung - Saputri, Septia Nur; Rifqi, Ahsanur; Darmalaksana, Wahyudin; Nur’aeni, Nur’aeni (Ma'soem University, 2023)
This research highlights the need for outstanding master students in scientific publications. This research uses a qualitative approach by applying methods that play a role in ensuring the formation of a collaboration strategy between lecturers and students. The results and discussion showed that the master student group seemed encouraged to exceed the productivity of scientific publications, achieve standards in article writing and scientific journal achievement, and strive to succeed by forming intensive classes that play a role in ensuring the formation of lecturer and student collaboration strategies. The conclusion of this study is that the master student group is proven to have the need to excel in the productivity of scientific publications.